2018
DOI: 10.2196/mhealth.9467
|View full text |Cite
|
Sign up to set email alerts
|

Satisfying Product Features of a Fall Prevention Smartphone App and Potential Users’ Willingness to Pay: Web-Based Survey Among Older Adults

Abstract: BackgroundProhibiting falls and fall-related injuries is a major challenge for health care systems worldwide, as a substantial proportion of falls occur in older adults who are previously known to be either frail or at high risk for falls. Hence, preventive measures are needed to educate and minimize the risk for falls rather than just minimize older adults’ fall risk. Health apps have the potential to address this problem, as they enable users to self-assess their individual fall risk.ObjectiveThe objective o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…The first sample retrieved from Knobe et al included 163 older adults (mean age 80.4 years, SD 6.4) [31]. The second one retrieved from Rasche et al contains 96 older adults with a mean age of 63.8 years (SD 7.02) [32]. Table 1 shows relevant data retrieved from the 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first sample retrieved from Knobe et al included 163 older adults (mean age 80.4 years, SD 6.4) [31]. The second one retrieved from Rasche et al contains 96 older adults with a mean age of 63.8 years (SD 7.02) [32]. Table 1 shows relevant data retrieved from the 2 studies.…”
Section: Resultsmentioning
confidence: 99%
“…If 1 out of the 3 outcome parameters of the AFPS is used to determine a positive result, then sensitivity could be increased up to 93%, whereas specificity thereby decreases to 11%. Calculations based on the data retrieved from the study by Rasche et al [32] showed a sensitivity of 66.7% (specificity 88.1%) for the primary outcome parameter of the AFPS. If just 1 out of the 3 parameters is used to determine a positive result, the sensitivity was again 66.7%, with a specificity of 84.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fear of falling can also drive seniors to limit their activities, which can result in further physical decline, depression, and social isolation [ 30 ]. Fall detection technologies have improved in recent years; however, considering that 20-30% of falls are preventable [ 25 , 26 ], technologies are needed to predict and prevent falls [ 20 , 31 - 33 ].…”
Section: Introductionmentioning
confidence: 99%